A Study Of The Relationship Between TQM And Knowledge Sharing - Cheah, Weng Choong (2008)
The purpose of this study is to investigate the six dimensions in total quality management (TQM), namely; leadership, organizational culture, teamwork, training and development, reward system, and customer focus and their effects on the knowledge sharing behavior among Malaysian employees.